Factors determining the performance of the automotive industry in Morocco: a qualitative study - DAHMANY Abdellah; AISSAOUI Nawfal; TOMAS Mounya; OUTOUGANE El Hossain; HASNAOUI Rachid (African Scientific Journal, 2024)
Résumé L’industrie automobile marocaine s’est imposée comme un pilier central de l’économie nationale et un moteur clé de l’industrialisation. L’objectif de cet article est de montrer comment les principaux acteurs de l’industrie automobile marocaine perçoivent les facteurs essentiels qui influencent la performance du secteur. Pour ce faire, les auteurs se sont basés sur une méthodologie qualitative, en utilisant des entretiens semi-structurés afin de collecter les informations auprès de huit professionnels et experts dans le domaine. Les résultats obtenus confirment l’importance des conditions politiques, institutionnelles et économiques spécifiques, ainsi que de la promotion du capital humain, de l’acceptation de la technologie, des ressources naturelles, de l’infrastructure et de la disponibilité du financement. Mots clés : Industrialisation ; industrie automobile ; croissance économique ; infrastructures, capital humain ; facteurs économiques. Abstract The moroccan automotive industry has established itself as a central pillar of the national economy and a key driver of industrialization. The objective of this article is to demonstrate how the principal stakeholders in the Moroccan automotive industry perceive the keys factors influencing the sector’s performance. To do this, the authors employed a qualitative methodology, utilizing semi-structured interviews to collect information from eight professionals and experts in the field. The findings corroborate the significance of particular political, institutional and economic conditions, in addition to the advancement of human capital, the endorsement of technology, natural resources, infrastructure and the accessibility of finance. Keywords: Industrialization; automotive industry; economic growth; infrastructure, human capital; economic factors.